Download as pdf or txt
Download as pdf or txt
You are on page 1of 22

MTCA4001 | Engineering Mathematics 2

Chapter 1 The Laplace Transform


1 Learning Outcomes
By the end of this topic you will be able to:

o Understand the Laplace Transform and its properties,


o Apply the Laplace Transform to a variety of functions,
o Perform Inverse Laplace Transform on certain functions, and
o Use the Laplace Transform to solve certain differential equations, including those with
engineering applications.

2 Introduction: The Laplace Transform


The Laplace transform is a mathematical integral of a particular form named after the French
mathematician Pierre Simon Laplace, who studied them in the late 18th century. In particular, the
Laplace Transform can be used to solve differential equations. It does this by transforming those
differential equations, which are difficult to solve, into algebraic equations which are far easier.
Because differential equations appear throughout many branches of engineering, it is a useful tool
for engineering students.

3 Definition of the Laplace Transform


The Laplace Transform is a specific improper integral of a function given by the following equation:

L{𝑓(𝑡)} = ∫ 𝑒 −𝑠𝑡 𝑓(𝑡)𝑑𝑡 3.1
0

The integral is called improper as the one of limits of the integral is infinity, which means that the
limit of the indefinite as the integral tends to infinity must be evaluated.
∞ 𝑘
∫ 𝑒 −𝑠𝑡 𝑓(𝑡)𝑑𝑡 = lim (∫ 𝑒 −𝑠𝑡 𝑓(𝑡)𝑑𝑡) 3.2
0 𝑘→∞ 0

Additionally, in order for some integrals to exist, it may be necessary to place some constraints on
the variable 𝑠, see Example 3.1 .

1
MTCA4001 | Engineering Mathematics 2

Example 3.2
Find the Laplace Transform of the following functions:
(a) 𝟏
(b) 𝒆−𝒂𝒕
∞ ∞
(a) (b)
L{1} = ∫ 𝑒 −𝑠𝑡 × 1 𝑑𝑡 L{𝑒 −𝑎𝑡 } = ∫ 𝑒 −𝑠𝑡 𝑒 −𝑎𝑡 𝑑𝑡
0 0
𝑘 𝑘
= lim (∫ 𝑒 −𝑠𝑡 𝑑𝑡) = lim (∫ 𝑒 −(𝑠+𝑎)𝑡 𝑑𝑡)
𝑘→∞ 0 𝑘→∞ 0
−𝑠𝑡 𝑘 −(𝑠+𝑎)𝑡 𝑘
𝑒 𝑒
= lim ( | ) = lim ( | )
𝑘→∞ −𝑠 𝑘→∞ −(𝑠 + 𝑎)
0 0
𝑒 −𝑠𝑘 𝑒 −𝑠×0 𝑒 −(𝑠+𝑎)𝑘 𝑒 −(𝑠+𝑎)×0
= lim ( − (− )) = lim ( − (− ))
𝑘→∞ −𝑠 𝑠 𝑘→∞ −(𝑠 + 𝑎) 𝑠+𝑎
1 1
=0+ = , 𝑠>0 1 1
𝑠 𝑠 =0+ = ,
(𝑠 + 𝑎) (𝑠 + 𝑎)
𝑠+𝑎 >0

MATLAB
Calculating the Laplace F (s) transform of a function f(t) is quite simple in Matlab. First you need to
specify that the variable t and s are symbolic ones. This is done with the command
>> syms t s % This is used to define symbolic function with t and s
variables

Next you define the function f(t). The actual command to


calculate the transform is

>> F=laplace(f,t,s)% uses the specified independent variable


t and s respectively

laplace(f) %returns the Laplace transform of f using the


default independent variable t and the default transformation
variable s.

Note: If you also do not specify the transformation variable,


laplace uses the variable s by default

Some examples

syms x y
f = x^2;
laplace(f, x, y)

ans =

2/y^3

2
MTCA4001 | Engineering Mathematics 2

Compute the Laplace transform of this expression calling the


laplace function with one argument. If you do not specify the
independent variable, laplace uses the variable t.
syms t y
f = exp(-2*t);
laplace(f, y)

ans =
1/(2 + y)

If you also do not specify the transformation variable,


laplace uses the variable s:

laplace(f)

ans =
1/(2 + s)

In some cases, the original function f(t) may have multiple


variables. In such cases, the variables should be included in
syms. For example, in the above example f(t)= e-at where “a”
is a variable which should be declared in syms. The code for
this laplace transform can be written as:

syms a t s
f=exp(-a*t);
F=laplace(f,t,s)

F=1/(a+s)

To make the expression more readable one can use the


commands, simplify and pretty. here is an example for the
function f(t),
f (t)= f=1+2*t*exp(-3*t)+4*exp(-3*t);

>> syms t s
>> f= f=1+2*t*exp(-3*t)+4*exp(-3*t);
>> F=laplace(f,t,s)

F =
4/(s + 3) + 2/(s + 3)^2 + 1/s

>> simplify(F)
ans =
(5*s^2 + 20*s + 9)/(s*(s + 3)^2)

>> pretty(ans)

3
MTCA4001 | Engineering Mathematics 2

5 s + 20 s + 9
---------------
2
s (s + 3)

Alternatively, one can write the function f(t) directly as


part of the laplace command:

>>F2=laplace(1+2*t*exp(-3*t)+4*exp(-3*t))

4 Properties of the Laplace Transform


The Laplace Transform has some basic properties which are explained in this section. Those
properties are referred to as:
 Linearity
 The First Shift Theorem
 The Second Shift Theorem

These properties are useful to know in order to break complex functions into simpler elements in
order to calculate their Laplace Transform.

4.1 Linearity
The Laplace Transform is simply a definite integral, and so the properties of definite integrals also
apply to them. One of these properties is that of linearity. That the Laplace Transform is a linear
operator has two important consequences:
 The Laplace Transform of the sum of two functions is equal to the sum of the Laplace
Transforms of the functions, and

L{𝑓 + 𝑔} = L{𝑓} + L{𝑔} 4.1

 A constant scalar of upon a function to be transformed can be taken outside of the


transform operation.

L{𝑘𝑓} = 𝑘L{𝑓} 4.2

 The Laplace transform of a product is not the product of the transforms.


L{𝑓 × 𝑔} ≠ L{𝑓} × L{𝑔}

Example 4.1
Use the linear properties of the Laplace Transform in order to transform the following functions:
(a) 𝟑
(b) 𝟓𝒆−𝒂𝒕 + 𝟒𝒆−𝒃𝒕

4
MTCA4001 | Engineering Mathematics 2

(a) L{3} = 3 × L{1} (b) L{5𝑒 −𝑎𝑡 + 4𝑒 −𝑏𝑡 } = 5 × L{𝑒 −𝑎𝑡 } + 4 × L{𝑒 −𝑏𝑡 }
1 1 1
=3×( ) =5×( )+4×( )
𝑠 𝑠+𝑎 𝑠+𝑏
3 5 4
= , 𝑠>0 = + ,
𝑠 (𝑠 + 𝑎) (𝑠 + 𝑏)
𝑠 > −𝑎, 𝑠 > −𝑏

4.2 First Shift Theorem


It can be shown that when an exponential function 𝑒 −𝑎𝑡 multiplies 𝑓(𝑡) the function to be
transformed, it shifts the Laplace Transform of the function by 𝑎.

L{𝑒 −𝑎𝑡 𝑓(𝑡)} = 𝐹(𝑠 + 𝑎) 4.3

Example 4.2

Given that L{𝒇(𝒕)} = 𝑭(𝒔) = ∫𝟎 𝒆−𝒔𝒕 𝒇(𝒕)𝒅𝒕, prove the First Shift Theorem:
L{𝒆−𝒂𝒕 𝒇(𝒕)} = 𝑭(𝒔 + 𝒂)


L{𝒆−𝒂𝒕 𝒇(𝒕)} = ∫ 𝒆−𝒂𝒕 𝒆−𝒔𝒕 𝒇(𝒕)𝒅𝒕
𝟎

= ∫ 𝒆−𝒔𝒕−𝒂𝒕 𝒇(𝒕)𝒅𝒕
𝟎

= ∫ 𝒆−(𝒔+𝒂)𝒕 𝒇(𝒕)𝒅𝒕
𝟎
= 𝑭(𝒔 + 𝒂)

Ex 4.2(a)
L{𝑒 −4𝑡 𝑡 6 } =?

Here, a=4, and 𝑔(𝑡) = 𝑡 6


Now,
L{𝒈(𝒕)} = L{𝑡 6 }
𝟔!
= 𝟕 𝒇𝒓𝒐𝒎 𝒕𝒂𝒃𝒍𝒆
𝒔
So,
𝟔!
L{𝑒 −4𝑡 𝑡 6 } =
(𝒔 − 𝟒)𝟕

5
MTCA4001 | Engineering Mathematics 2

Ex 4.2(b)
Find the Laplace transform of the function 𝒇(𝒕) = (𝒕 + 𝟏)𝟐 𝒆𝒕

Here, a=-1, and 𝑔(𝑡) = (𝑡 + 1)2


Now,
L{𝒈(𝒕)} = L{(𝑡 + 1)2 𝑡 6 }
= L{𝑡 2 + 2𝑡 + 1}
= L{𝑡 2 } + L{2𝑡}+L{1}

𝟐! 𝟏! 𝟏
= + + 𝒇𝒓𝒐𝒎 𝒕𝒂𝒃𝒍𝒆
𝒔𝟑 𝒔𝟐 𝒔
So,
𝟐 𝟏 𝟏
L{(𝒕 + 𝟏)𝟐 𝒆𝒕 } = 𝟑
+ 𝟐
+
(𝒔 − 𝟏) (𝒔 − 𝟏) (𝒔 − 𝟏)

4.3 Second Shift Theorem (Time Shift)


Similarly to the First Shift Theorem above, when an exponential function 𝑒 −𝑑𝑡 multiplies the Laplace
Transform of a function 𝐹(𝑠), shifts the function to be transformed by −𝑑.

𝑒 −𝑠𝑑 𝐹(𝑠) = L{𝑢(𝑡 − 𝑑)𝑓(𝑡 − 𝑑)} 4.4

Additionally, the function is scaled by the time-shifted Heaviside step function 𝑢(𝑡 − 𝑑), which is
utilized to simply zero the function appropriately.

1, 𝑡≥0
𝑢(𝑡) = { 4.5
0, 𝑡<0

Figure 1: A function shifted in time by 𝑑.

6
MTCA4001 | Engineering Mathematics 2

If 𝒈(𝒕) has Laplace transform 𝑮(𝒔) then the shifted function


𝒖(𝒕 − 𝒂)𝒈(𝒕 − 𝒂)
has Laplace transform
𝒆−𝒂𝒔 𝑮(𝒔)
Note: 𝒖(𝒕 − 𝒂) is called heaviside step function.

Proof:

L{𝒖(𝒕 − 𝒂)𝒈(𝒕 − 𝒂)} = ∫ 𝒆−𝒔𝒕 𝒖(𝒕 − 𝒂)𝒈(𝒕 − 𝒂)𝒅𝒕
𝟎
𝒂 𝒂 ∞
−𝒔𝒕
𝟏
= ∫ 𝟎𝒅𝒕 + ∫ 𝒆 𝒈(𝟎)𝒅𝒕 + ∫ 𝒆−𝒔𝒕 𝟏𝒈(𝒕 − 𝒂)𝒅𝒕
𝟎 𝒂 𝟐 𝒂

= 𝟎 + 𝟎 + ∫ 𝒆−𝒔𝒕 𝟏𝒈(𝒕 − 𝒂)𝒅𝒕
𝒂
Let 𝒒 = 𝒕 − 𝒂
𝒅𝒒 = 𝒅𝒕

= ∫ 𝒆−𝒔(𝒒+𝒂) 𝒈(𝒒)𝒅𝒒
𝟎

−𝒔𝒂
=𝒆 ∫ 𝒆−𝒔𝒒 𝒈(𝒒)𝒅𝒒
𝟎
= 𝒆−𝒔𝒂 𝑮(𝒔)

Proof:


L[ f (t  a )u (t  a )]   f (t  a )e  st
a

Let x  t  a, then dx  dt and t  x  a


As t  a, x  0 and as t  , x  . So, L[ f (t  a)u (t  a)]  e  as F ( s)
 


0
f ( x)e  s ( x  a ) dx  e  as  f ( x)e  sx dx
0

Example:
Determine the Laplace transform of
𝒖(𝒕 − 𝟒)(𝒕 − 𝟒)

So, here a=4


And
𝒈(𝒕) = 𝒕
L{𝒈(𝒕)} = L{𝒕}
𝟏
= 𝟐
𝒔
So, Laplace transorm of 𝒖(𝒕 − 𝟒)(𝒕 − 𝟒) 𝒃ased on second shifting theorem

7
MTCA4001 | Engineering Mathematics 2

𝟏
L{𝒖(𝒕 − 𝟒)(𝒕 − 𝟒) } = 𝒆−𝟒𝒔
𝒔𝟐

5 Laplace Transform of Common Functions


Typically when finding the Laplace Transform of a function, the normal procedure is not typically to
evaluate the integral given by Equation. Instead, a table of Laplace Transform of a various functions
is consulted and properties of the Laplace Transform are used in order to determine the result.
Table 1 is such a table.

Function Laplace Transform Function Laplace Transform


𝒇(𝒕) L{𝒇(𝒕)} 𝒇(𝒕) L{𝒇(𝒕)}
1 2𝑏𝑠
𝟏 𝑡 sin 𝑏𝑡
𝑠 (𝑠 2 + 𝑏 2 )2
1 𝑠 2 − 𝑏2
𝒕 𝑡 cos 𝑏𝑡
𝑠2 (𝑠 2 + 𝑏 2 )2
2 𝑏
𝒕𝟐 sinh 𝑏𝑡
𝑠3 𝑠2 − 𝑏2
𝑛! 𝑠
𝒕𝒏 cosh 𝑏𝑡
𝑠 𝑛+1 𝑠 2 − 𝑏2
𝑏 1
𝐬𝐢𝐧 𝒃𝒕 𝑢(𝑡)
𝑠 + 𝑏2
2 𝑠
𝑠
𝐜𝐨𝐬 𝒃𝒕 𝛿(𝑡) 1
𝑠 2 + 𝑏2
Table 1. A table of the Laplace Transforms of various functions.
Example 5.1 demonstrates how the information within the previous sections can be combined to
determine the Laplace Transform of a complicated function.

dirac(x) represents the Dirac delta function of x.

MATLAB
In MATLAB, dirac(t) represents the Dirac delta function of t [(t)]. And, heaviside(t) is used to
present the unit step (u(t)) function of t.

To represent any constant term in the function, heaviside(t) should be used during Laplace
transform. We know from the table that L{1}=1/s and L{(t)}=1.

8
MTCA4001 | Engineering Mathematics 2

>> laplace(dirac(t))

ans =

>> laplace(heaviside(t))

ans =

1/s

Another example, f(t)=5+4te-2t

>> Ft=5* heaviside(t)+4*t*exp(-2*t);


laplace(Ft,t,s)

ans =

4/(s + 2)^2 + 5/s

Example 5.1
Find the Laplace Transform of the following function.
𝒕
𝟏𝟎𝒆−𝟓𝒕 𝐬𝐢𝐧
𝟐

9
MTCA4001 | Engineering Mathematics 2

𝑡
L {10𝑒 −5𝑡 sin }
2

We calculate this transform by:


 reducing it to simpler elements,
 referring to the chart of Laplace Transforms, and
 applying their different properties.
First, we recognise that the function to be transformed is a scalar 10 multiplying an exponential
t
function e−5t which multiplies a sine function sin 2. Each of these elements can be handled
separately.
1
𝑡 2
L {sin } = Table 1 tells us the Laplace transform of a sine
2 1 2
𝑠2 + ( ) function.
2
2 𝑏
= 2 L{sin 𝑏𝑡} = 2
4𝑠 + 1 𝑠 + 𝑏2

𝑡 𝑡 The First Shift Theorem explains that


L {𝑒 −5𝑡 sin } = L {sin } (𝑠 + 5) multiplication by an exponential function shifts
2 2
2 the Laplace transform.
=
4(𝑠 + 5)2 + 1
𝐿{𝑒 −𝑎𝑡 𝑓(𝑡)} = 𝐹(𝑠 + 𝑎)

𝑡 2 Multiplication by a constant scalar can be taken


L {10𝑒 −5𝑡 sin } = 10 × outside of the Laplace Transform because of its
2 4(𝑠 + 5)2 + 1
20 linear properties.
=
4(𝑠 + 5)2 + 1
L{𝑘𝑓(𝑡)} = 𝑘L{𝑓(𝑡)}

Applying these results together allows us to find the final answer to the original problem:
𝑡 20
L {10𝑒 −5𝑡 sin } =
2 4(𝑠 + 5)2 + 1
20
= 2
4(𝑠 + 10𝑠 + 25) + 1
20
= 2
4𝑠 + 40𝑠 + 101

6 Inverse Laplace Transform


The Inverse Laplace Transform is the operation which turns an 𝑠-domain equation into a 𝑡-domain
equation. Mathematically, this is written:

L−1 {𝐹(𝑠)} = 𝑓(𝑡) 6.1

Determining the Inverse Laplace Transform is not usually calculated typically done by consulting a
table and incorporating various properties. The key property is linearity:

10
MTCA4001 | Engineering Mathematics 2

L−1 {𝑎𝐹(𝑠) + 𝑏𝐺(𝑠)} = 𝑎L−1 {𝐹(𝑠)} + 𝑏L−1 {𝐺(𝑠)} 6.2

This allows us to break up complex Inverse Laplace Transform Problems into simpler constituent
problems, which we can manipulate to fit with our table and then solve.

Example 6.1
Determine the Inverse Laplace Transform of the following expression:
𝟑 𝟗𝒔 𝟏
𝑭(𝒔) = + 𝟐 +
𝒔 𝒔 +𝟒 𝒔−𝟐
In order to find a solution, we apply the Inverse Laplace Transform to both sides of the equation
and use the properties of linearity to break the problem up into smaller simpler pieces. We also
inspect the equation to see if some manipulating of the individual expression can lead us to more
closely match our table of Laplace Transforms.
−1 −1 3 9𝑠 1
L {𝐹(𝑠)} = L { + 2 + }
𝑠 𝑠 +4 𝑠−2
−1 1 −1 𝑠 −1 1
𝑓(𝑡) = 3L { } + 9L { 2 }+L { }
𝑠 𝑠 +4 𝑠−2
−1 1 −1 𝑠 −1 1
= 3L { } + 9L { 2 2 }+L { }
𝑠 𝑠 +2 𝑠−2
We now consult the table in order to transform these equations. We see there that:
1 𝑠 1
L{1} = L{cos 𝑏𝑡} = 2 2 L{𝑒 𝑎𝑡 } =
𝑠 𝑠 +𝑏 𝑠−𝑎
Thus:
𝑓(𝑡) = 3 + 9 cos 2𝑡 + 𝑒 2𝑡

Example 6.2
Determine the Inverse Laplace Transform of the following expression:
𝟗𝒔 𝟗
𝑮(𝒔) = 𝟐 + 𝟐
𝒔 + 𝟐𝟓 𝟕𝒔 + 𝟕

Similarly to the last problem, we apply the Inverse Laplace Transform to both sides of the
equation and use the properties of linearity to break the problem up into smaller simpler pieces.

𝟗𝒔 𝟗
L−𝟏 {𝑮(𝒔)} = L−𝟏 { + 𝟐 }
𝒔𝟐
+ 𝟐𝟓 𝟕𝒔 + 𝟕
−𝟏 𝒔 𝟗 −𝟏 𝟏
𝒈(𝒕) = 𝟗L { 𝟐 𝟐 }+ L { 𝟐 }
𝒔 +𝟓 𝟕 𝒔 + 𝟏𝟐
We now consult the table in order to transform these components. We see there that:
𝒔 𝑏
L{𝐜𝐨𝐬 𝒃𝒕} = L{sin 𝑏𝑡} =
𝒔𝟐 + 𝒃𝟐 𝑠2 + 𝑏2
Thus:
𝟗
𝒈(𝒕) = 𝟗 𝐜𝐨𝐬 𝟓𝒕 + 𝐬𝐢𝐧 𝒕
𝟕

Example 6.3
Determine the Inverse Laplace Transform of the following expression:

11
MTCA4001 | Engineering Mathematics 2

𝟑
𝑯(𝒔) =
𝒔𝟐 + 𝟖𝒔 + 𝟐𝟓

In this problem, we will see that the denominator does not have an obvious corresponding entry
in the table. In order to find the inverse transform, we will be required to complete the square
and then to apply the First Shift Theorem in order to find the 𝒕-domain function we are seeking.

𝟑
L−𝟏 {𝑯(𝒔)} = L−𝟏 { }
𝒔𝟐 + 𝟖𝒔 + 𝟐𝟓
𝟑
𝒉(𝒕) = L−𝟏 { 𝟐 }
(𝒔 + 𝟖𝒔 + 𝟏𝟔) + 𝟗
−𝟏 𝟑
=L { }
(𝒔 + 𝟒)𝟐 + 𝟑𝟐
We now consult the table in order to transform these components and remember the First Shift
Theorem. We see there that:
𝒃
L{𝐬𝐢𝐧 𝒃𝒕} = L{𝑒 −𝑎𝑡 𝑓(𝑡)} = 𝐹(𝑠 + 𝑎)
𝒔𝟐
+ 𝒃𝟐
Combining these results shows us that:
𝒃
L{𝒆−𝒂𝒕 𝐬𝐢𝐧 𝒃𝒕} =
(𝒔 + 𝒂)𝟐 + 𝒃𝟐
Thus:
𝒉(𝒕) = 𝒆−𝟒𝒕 𝐬𝐢𝐧 𝟑𝒕

MATLAB
ilaplace(F) returns the inverse Laplace transform of F using the default independent variable s for
the default transformation variable t.

>>syms t,s
>> F=1/(s-2);
>> ilaplace(F)
ans =
exp(2*t)

ilaplace(F,transVar) uses the specified transformation


variable transVar instead of t.

>> syms x s
>> F=1/(s-2);
>> ilaplace(F,x)

ans =

exp(2*x)

When the function is complicated, it is often required to


have simplification.

syms t s

12
MTCA4001 | Engineering Mathematics 2

F=(1.25*s^2+2*s-5)/(s^3*(s^2-s)^2);
ft=ilaplace(F,t)
Ft=simplify(ft)
pretty(ft)

ft =

(53*exp(t))/4 - (23*t)/2 - (7*t*exp(t))/4 - (39*t^2)/8 -


(4*t^3)/3 - (5*t^4)/24 - 53/4

Ft =

(53*exp(t))/4 - (23*t)/2 - (7*t*exp(t))/4 - (39*t^2)/8 -


(4*t^3)/3 - (5*t^4)/24 - 53/4

2 3 4
53 exp(t) 23 t 7 t exp(t) 39 t 4 t 5 t
--------- - ---- - ---------- - ----- - ---- - ---- - 53/4
4 2 4 8 3 24

MATLAB Class activity

A function is given by f(t)= 2t+3t^2e-3t+4e-2t


(i) Find Laplace Transform of f(t), that is find F(s)
(ii) Simplify F(s) and the use the command ‘pretty’
(iii) Find the Inverse Laplace Transform of F(s), that is find f(t)
(iv) Show that f(t) as found from part (c) is the same as the given f(t)

6.1 Partial Fractions


Some Inverse Laplace Transforms do not easily fit a form recognisable in the table, and more
complicated manipulations are necessary to be able to transform them. One such technique in
these cases is separation into partial fractions.

Example 6.4
Determine the Inverse Laplace Transform of the following expressions using Partial Fractions:
7s − 6
F(s) = 2
s −s−6

13
MTCA4001 | Engineering Mathematics 2

At first glance this problem seems difficult to determine because it doesn’t fit with any of the
transforms of our table. However, we can see that by factorizing the denominator and separating
into partial fractions, we can find a straightforward solution.

7𝑠 − 6
𝐹(𝑠) =
𝑠2 − 𝑠 − 6
7𝑠 − 6
=
(𝑠 + 2)(𝑠 − 3)
𝐴 𝐵
= +
(𝑠 + 2) (𝑠 − 3)
7𝑠 − 6 𝐴(𝑠 − 3) + 𝐵(𝑠 + 2)
=
(𝑠 + 2)(𝑠 − 3) (𝑠 + 2)(𝑠 − 3)

𝐴(𝑠 − 3) + 𝐵(𝑠 + 2) = 7𝑠 − 6 𝐴(𝑠 − 3) + 𝐵(𝑠 + 2) = 7𝑠 − 6


𝑠 = −2 → −5𝐴 = −20 𝑠 = 3 → 5𝐵 = 15
𝐴=4 𝐵=3
4 3
𝐹(𝑠) = +
(𝑠 + 2) (𝑠 − 3)
In this different form, the Inverse Laplace Transform can be found as before, i.e. applying the
properties of linearity and breaking into smaller sub-problems.
−1 −1 4 3
L {𝐹(𝑠)} = L { + }
(𝑠 + 2) (𝑠 − 3)
−1 1 −1 1
𝑓(𝑡) = 4L { } + 3L { }
𝑠+2 𝑠−3
= 4𝑒 −2𝑡 + 3𝑒 3𝑡

14
MTCA4001 | Engineering Mathematics 2

6 Laplace Transform of Derivatives


This section will show that the Laplace Transform of the derivative and integral of a function takes
on a special form. In fact, it changes differential equations into algebraic equations. Additionally, it
also incorporates time values of the time function which will allow us to easily incorporate initial
conditions in differential equations problems. This can greatly simplify the procedure of solving
differential equations.

6.2 Derivatives
A formula for the Laplace Transform of the derivative of a function f'(t) can be derived using
Integration by Parts.

L{𝑓′(𝑡)} = ∫ 𝑒 −𝑠𝑡 𝑓′(𝑡)𝑑𝑡
0

We approach this a problem of integration by parts, the formula of which is:

∫ 𝑢 𝑑𝑣 = 𝑢𝑣 − ∫ 𝑣 𝑑𝑢

We then must choose from our substitutions.


𝑢 = 𝑒 −𝑠𝑡
𝑑𝑢 ∫ 𝑑𝑣 = ∫ 𝑓 ′(𝑡) 𝑑𝑡
= −𝑠𝑒 −𝑠𝑡
𝑑𝑡 𝑣 = 𝑓(𝑡)
𝑑𝑢 = −𝑠𝑒 −𝑠𝑡 𝑑𝑡
Slotting 𝑢, 𝑣, and 𝑑𝑢 into our equation gives us:
∞ ∞
∫ 𝑒 −𝑠𝑡 𝑓 ′ (𝑡)𝑑𝑡 = lim (𝑒 −𝑠𝑡 𝑓(𝑡)|𝑘0 ) − ∫ 𝑓(𝑡)(−𝑠𝑒 −𝑠𝑡 )𝑑𝑡
0 𝑘→∞ 0

−𝑠𝑘 −𝑠×0
= lim (𝑒 𝑓(𝑘) − 𝑒 𝑓(0)) + 𝑠 ∫ 𝑒 −𝑠𝑡 𝑓(𝑡)𝑑𝑡
𝑘→∞ 0
= 0 − 1 × 𝑓(0) + 𝑠𝐹(𝑠)
= 𝑠𝐹(𝑠) − 𝑓(0), 𝑠<0
lim (𝑒 −𝑠𝑘 𝑓(𝑘)) = 0 is valid provided that the exponential function goes to zero faster than the
𝑘→∞
function 𝑓 rises.

The final result is restated:


L{𝑓′(𝑡)} = 𝑠𝐹(𝑠) − 𝑓(0) 0.1
A pattern emerges when analysing the Laplace Transform of higher order derivatives.
L{𝑓(𝑡)} = 𝐹(𝑠)
L{𝑓 ′ (𝑡)} = 𝑠𝐹(𝑠) − 𝑓(0)
L{𝑓 ′′ (𝑡)} = 𝑠 2 𝐹(𝑠) − 𝑠𝑓(0) − 𝑓 ′ (0)
⋮ 0.2
𝑛

L{𝑓 (𝑛) (𝑡)} = 𝑠 𝑛 𝐹(𝑠) − ∑ 𝑠 𝑛−𝑘 𝑓 (𝑘−1) (0)


𝑘=1

The following example shows how this can be applied to a differential equation.

15
MTCA4001 | Engineering Mathematics 2

Example 0.1
Express the following differential equation as an algebraic equation using the Laplace Transform.
𝒙′′ (𝒕) + 𝒙′(𝒕) + 𝒙(𝒕) = 𝟏

16
MTCA4001 | Engineering Mathematics 2

In order to find a solution, we apply the Laplace Transform to both sides of the equation.
L{𝑥 ′′ (𝑡) + 𝑥′(𝑡) + 𝑥(𝑡)} = L{1}
1
L{𝑥 ′′ (𝑡)} + L{𝑥 ′ (𝑡)} + L{𝑥(𝑡)} =
𝑠
We use the results seen above to evaluate the Laplace Transform of the various derivatives and
function itself.
1
(𝑠 2 𝑋(𝑠) − 𝑠𝑥(0) − 𝑥′(0)) + (𝑠𝑋(𝑠) − 𝑥(0)) + 𝑋(𝑠) =
𝑠
The Laplace Transformation of the solution to the differential equation can then be stated in
terms of 𝑠 and the initial conditions 𝑥(0) and 𝑥 ′ (0) by simply solving this equation for 𝑋(𝑠):
1
𝑠 2 𝑋(𝑠) − 𝑠𝑥(0) − 𝑥′(0) + 𝑠𝑋(𝑠) − 𝑥(0) + 𝑋(𝑠) =
𝑠
2 ′ (0)
1
𝑠 𝑋(𝑠) + 𝑠𝑋(𝑠) + 𝑋(𝑠) = 𝑠𝑥(0) + 𝑥 + 𝑥(0) +
𝑠
2 ′ (0)
𝑠 𝑥(0) + 𝑠𝑥 + 𝑠𝑥(0) + 1
𝑋(𝑠)(𝑠 2 + 𝑠 + 1) =
𝑠

17
MTCA4001 | Engineering Mathematics 2

𝑠 2 𝑥(0) + 𝑠𝑥 ′ (0) + 𝑠𝑥(0) + 1


𝑋(𝑠) =
𝑠(𝑠 2 + 𝑠 + 1)

MATLAB
Laplace transform of differentiation

The Laplace transform of a function is related to the Laplace transform of its derivative:

syms f(t) s
laplace(diff(f(t), t), t, s)

ans =
s*laplace(f(t), t, s) - f(0)

Or,
laplace(diff(sym('f(t)')))
ans =

s*laplace(f(t), t, s) - f(0)

Laplace transform of 2nd order differentiation can be found as:


Example, Laplace transform of 12y’’(t) [e.i., d2y(t)/dt2]
laplace(12*diff(sym('y(t)'),2))

ans =

12*s*(s*laplace(y(t),t,s)-y(0))-12*D(y)(0)

6.3 Integrals
Similarly, the Laplace Transform of the integral of a function with limits from 0 to 𝑡 can be written:
𝑡
1
L {∫ 𝑓(𝑡)𝑑𝑡} = 𝐹(𝑠) 0.3
0 𝑠

Using these tools, we can see that solving certain differential equations is made much easier – the
process of solving them is the same as algebraic equations – however, we do not yet have the tools
to revert the equation back to a function of 𝑡 – the solution is expressed as a function of 𝑠. This
technique we introduce in the next section.

18
MTCA4001 | Engineering Mathematics 2

7 Solving Differential Equations using the Laplace Transform


Piecing together the mathematical tools discussed previously in this chapter, it is clear that we can
use the Laplace domain to solve differential equations by the following steps:

1. Transform the differential equation using the Laplace Transform. (This step also included
initial conditions due to the Laplace Transform of a derivative, Equation 0.2.)
2. Solve the equation using algebraic rules for the function to be known.
3. Transform the 𝑠-variable solution back to the 𝑡-domain via the Inverse Laplace Transform.

The following example illustrates this procedure.

Example 7.1
Solve the following differential equation using the Laplace Transform method.
𝑑𝑦
+ 𝑦 = 1, 𝑦(0) = 0
𝑑𝑡
1. Transform the differential equation using the Laplace Transform
𝑑𝑦
+𝑦 =1
𝑑𝑡
𝑑𝑦
L { + 𝑦} = L{1}
𝑑𝑡
1
𝑠𝑌(𝑠) − 𝑦(0) + 𝑌(𝑠) =
𝑠

2. Solve the equation using algebraic rules for the function to be known.
1
𝑌(𝑠)(𝑠 + 1) =
𝑠
1
𝑌(𝑠) =
𝑠(𝑠 + 1)
3. Transform the 𝑠-variable solution back to the 𝑡-domain via the Inverse Laplace Transform.
1 𝐴 𝐵
= + 𝐴(𝑠 + 1) + 𝐵𝑠 = 1
𝑠(𝑠 + 1) 𝑠 (𝑠 + 1)
𝐴(𝑠 + 1) + 𝐵𝑠 𝑠 = −1 → 𝐵 = −1
= 𝑠=0→𝐴=1
𝑠(𝑠 + 1)
1 1 1
𝑌(𝑠) = = −
𝑠(𝑠 + 1) 𝑠 (𝑠 + 1)
1 1
L {𝑌(𝑠) } = L−1 { −
−1
}
𝑠 (𝑠 + 1)
1 1
𝑦(𝑡) = L−1 { } − L−1 { }
𝑠 (𝑠 + 1)
= 1 − 𝑒 −𝑡

8 Applications
We have seen that the Laplace Transform can be used to solve differential equations. This means
that this technique can be applied where suitable differential equations also appear – as differential
equations are often encountered in engineering, the Laplace Transform can be commonly applied.

19
MTCA4001 | Engineering Mathematics 2

8.1 Electrical Circuits


The laws which govern electrical circuits are described by differential equations. For example, the
voltage drop across a resistor, capacitor and inductor can be described by the following
relationships:

1 𝑡 𝑑𝑖
𝑉𝑅 = 𝑅𝑖 𝑉𝐶 = ∫ 𝑖 𝑑𝑡 𝑉𝐿 = 𝐿
𝐶 −∞ 𝑑𝑡

Kirchoff’s Voltage Law states that all voltages in a circuit loop must sum to zero. These physical laws
lead directly to differential equations which can be solved using the Laplace Transform:

𝑉 − 𝑉𝑅 − 𝑉𝐿 − 𝑉𝑐 = 0
𝑑𝑖 1 𝑡
𝑉 − 𝑅𝑖 − 𝐿 − ∫ 𝑖 𝑑𝑡 = 0
𝑑𝑡 𝐶 −∞

8.2 Mechanical Systems


Similarly to the voltage equations above, differential equations can be used to model mechanical
systems. For example, consider the motion of a mass attached to a dashpot and a spring as it
experiences a force.

𝑑𝑥 𝑑2 𝑥
𝐹𝐻 = −𝑘𝑥 𝐹𝐵 = −𝐵 𝐹𝑁 = 𝑚
𝑑𝑡 𝑑𝑡 2

As the net force is zero, the following differential equation can be written:

𝐹𝑁 + 𝐹𝐵 + 𝐹𝐻 = 0
2
𝑑 𝑥 𝑑𝑥
𝑚 2 −𝐵 − 𝑘𝑥 = 0
𝑑𝑡 𝑑𝑡

9 MATLAB
Using Matlab with Laplace transform:

20
MTCA4001 | Engineering Mathematics 2

 4t
Example 9.1 : Use Matlab to find the transform of te

The following is written in italic to indicate Matlab code

syms t,s

laplace(t*exp(-4*t),t,s)

ans =

1/(s+4)^2

Example 9.2 : Use Matlab to find the inverse transform of


s( s  6)
F ( s) 
( s  3)(s 2  6s  18)

The following is written in italic to indicate Matlab code

syms s t

ilaplace(s*(s+6)/((s+3)*(s^2+6*s+18)))

ans =

-exp(-3*t)+2*exp(-3*t)*cos(3*t)

10 Exercises
Below is a borderless table where each column is numbered separately. Unfortunately, it won’t
update automatically; the second column’s numbers has to be set to follow on from the first column.

𝑠−1
1. Given 𝐹(𝑠) = 𝑠2 +1 is the Laplace transform of 𝑓(𝑡), find the Laplace Transform of the
following:
5𝑓(𝑡)
a) 2𝑒 −5𝑡 𝑓(𝑡) c) 𝑒 −4𝑡

b) 6𝑢(𝑡 − 2)𝑓(𝑡 − 2) d) 7𝑒 −𝜋𝑡 𝑓(𝑡) + 1

21
MTCA4001 | Engineering Mathematics 2

2. Find the Inverse Laplace Transform of the following:

1 2 5 6𝑠
a) + + c) 𝑠2 +1
𝑠 𝑠+4 𝑠−3

4𝑠−6 𝑠−1
b) d) 𝑠2 +4𝑠+4
8𝑠2 +13𝑠+2

3. Solve the following differential equations using the Laplace Transform method.

𝑑2 𝑦 𝑑𝑦
a) 4 − 2 + 5𝑦 = 3
𝑑𝑡 𝑑𝑡
𝑑2 𝑦 𝑑𝑦
b) 𝑑𝑡
− 𝑑𝑡
+ 5𝑦 = cos 2𝜋𝑡

11 Chapter Summary
This chapter has explained the Laplace Transform and its properties. The Laplace Transform was
applied to many different functions, and it was shown how to perform and Inverse Laplace
Transform.

These techniques culminated with a demonstration of how the Laplace Transform could be used to
solve certain differential equations, including those which occur often in engineering problems.

22

You might also like